L’Émergence de l’esthétique photographique par Viollet-le-Duc et Ruskin - Arnaud François (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This article deploys the field of research on structuring sensitive experiences through "energetic images" to examine the influence of photography on architectural aesthetics during the second half of the nineteenth century. Using a quasi-archaeological approach, the article takes a case study of the works of Viollet-le-Duc and Ruskin, hypothesizing that photography unconsciously influenced their sense of perception and imagination to the point of renewing the art of architecture from this new aesthetic. In images, one finds that photography represents a praise of matter and of previous life. This poetry is also integrated into a structure of perception corresponding to photography: 1. the fragmentation of space, 2. the incarnation of the point of view by the dark room, 3. the urban condition of the building’s vision, 4. the homogeneity of the details and the photographic grain. The article ends by revealing Frank Lloyd Wright’s and Le Corbusier’s rejection of photographic aesthetics of the 19th century in the name of a new vision, this time unconsciously structured by cinema.